An Approach of the Maximum Curvature Measurement of Dynamic Umbilicals Using OFDR Technology in Fatigue Tests - Yin, Yuanchao; Yu, Peng; Jia, Ziguang; Wu, Shanghua; Lu, Qingzhen; Yan, Jun; Yue, Qianjin (Frontiers in Materials, 2021)
Prototype fatigue tests simulate in-place working condition of dynamic umbilicals which are usually conducted to verify the fatigue life. The fatigue failure hot spot locates on the top segment of the umbilical. The umbilical reaches a maximum curvature at the hot spot. The hot spot position of the umbilical is always inside or near the bend stiffener. The radial gap between the umbilical and the bend stiffener is very small, which makes it difficult to put traditional sensors in the gap. In this work, a prototype umbilical tension-bending test is conducted, and the optic frequency domain reflectometer (OFDR) technology is utilized to measure the distributed strain of the umbilical inside the bend stiffener. The curvature of the umbilical is obtained to locate the fatigue hot spot in order to verify the feasibility of this approach. The test results show that the umbilical curvature can be measured well with the use of OFDR technology. The influence of tension and swing angle on the position of the maximum curvature is studied. The method proposed in this paper provides a valuable approach for curvature monitoring in the application of dynamic umbilical fatigue tests.